International Consensus Guidance for Management of Myasthenia Gravis: 2020 Update. (19th January 2021) - Narayanaswami, Pushpa; Sanders, Donald B.; Wolfe, Gil; Benatar, Michael; Cea, Gabriel; Evoli, Amelia; Gilhus, Nils Erik; Illa, Isabel; Kuntz, Nancy L.; Massey, Janice; Melms, Arthur; Murai, Hiroyuki; et al.
Abstract : Objective: To update the 2016 formal consensus-based guidance for the management of myasthenia gravis (MG) based on the latest evidence in the literature. Methods: In October 2013, the Myasthenia Gravis Foundation of America appointed a Task Force to develop treatment guidance for MG, and a panel of 15 international experts was convened. The RAND/UCLA appropriateness method was used to develop consensus recommendations pertaining to 7 treatment topics. In February 2019, the international panel was reconvened with the addition of one member to represent South America. All previous recommendations were reviewed for currency, and new consensus recommendations were developed on topics that required inclusion or updates based on the recent literature. Up to 3 rounds of anonymous e-mail votes were used to reach consensus, with modifications to recommendations between rounds based on the panel input. A simple majority vote (80% of panel members voting "yes") was used to approve minor changes in grammar and syntax to improve clarity. Results: The previous recommendations for thymectomy were updated. New recommendations were developed for the use of rituximab, eculizumab, and methotrexate as well as for the following topics: early immunosuppression in ocular MG and MG associated with immune checkpoint inhibitor treatment. Conclusion: This updated formal consensus guidance of international MG experts, based on new evidence, provides recommendations to clinicians caring for patients with MG worldwide.